Experimental Study on the comparison of antibacterial and antioxidant effects between the Bee Venom and Sweet Bee Venom - Joong chul An; Ki Rok Kwon; Eun Hee Lee; Bae Chun Cha (Korean Pharmacopuncture Institute, 2006)
Objectives : This study was conducted to compare antibacterial activities and free radical scavenging activity between the Bee Venom and Sweet Bee Venom in which the allergy-causing enzyme is removed. Methods : To evaluate antibacterial activities of the test samples, gram negative E. coli and gram positive St. aureus were compared using the paper disc method. For comparison of the antioxidant effects, DPPH (1,1-diphenyl-2-picrylhydrazyl) free radical scavenging assay and Thiobarbituric Acid Reactive Substances (TBARS) assay were conducted. Results : 1. Antibacterial activity against gram negative E. coli was greater in the Sweet Bee Venom group than the Bee Venom group. 2. Antibacterial activity against gram positive St. aureus was similar between the Bee Venom and Sweet Bee Venom groups. 3. DPPH free radical scavenging activity of the Bee Venom group showed 2.8 times stronger than that of the Sweet Bee Venom group. 4. Inhibition of lipid peroxidation of the Bee Venom group showed 782 times greater than that of the Sweet Bee Venom group. Conclusions : The Bee Venom group showed outstanding antibacterial activity against gram positive St. aureus, and allergen-removed Sweet Bee Venom group showed outstanding antibacterial activity against both gram negative E. coli and gram positive St. aureus. For antioxidant effects, the Bee Venom was superior over the Sweet Bee Venom and the superiority was far more apparent for lipid peroxidation.